An in vivo model to study the anti-malaric capacity of plant extracts - Chinchilla, Misael (Universidad de Costa Rica, 1998)
An in vivo model to study lhe antimalarie ctfeet 01' plant extraets is described. White mi ce (25-30g body weight) are lreated subeutaneously with 0.6ml of the diluted extraet stUlling seven days before P. ber¡:heí infeetion: trealmenl eontinlles lIntil death or for 30 days. Simultaneously 0.2ml of the extraet are applied per os stming three days befare infection. In a test 01' the model, treated and non-treated animals differed in body weight, survival time, haematocrite, parnsitemia development, and spleen or liver weight of recent dcad 01' killed mice.